Sistem Informasi Administrasi Pembayaran Siswa Berbasis Web di SMK Bina Insan Nusantara - Nisya Istiqomah Arifin; Muhamad Alfarel Julianto; Muhamad Miqbad Attamami; Janu Ilham Saputro (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study addresses the inefficiencies in the manual student payment administration system currently used at SMK Bina Insan Nusantara, which relies on handwritten ledgers and Microsoft Excel spreadsheets, leading to frequent data errors, delayed reporting, and difficulties in retrieving payment records. The research aims to design a web-based information system to streamline the recording, monitoring, and reporting of student payments. A descriptive research approach was employed, with data collected through direct observation, semi-structured interviews with administrative staff, and literature review. System analysis was conducted using the PIECES framework, and system design followed the Unified Modeling Language (UML) methodology. The proposed system features user authentication, student data management, real-time payment input, digital receipt generation, and automated reporting (daily, monthly, and yearly). Black-box testing confirmed that the system functions as intended, validating inputs, processing transactions accurately, and generating reliable outputs. Findings indicate that the web-based system significantly improves data accuracy, operational efficiency, accessibility, and service quality compared to the existing manual process. The implementation of this system enables school administrators to manage payments more effectively, provides students and parents with timely access to payment information, and supports faster, data-driven decision-making by school leadership and the foundation. Future enhancements could include mobile integration and online payment gateways.